2007
DOI: 10.1103/physreva.75.053408
|View full text |Cite
|
Sign up to set email alerts
|

H3+molecular ion in a magnetic field: Linear parallel configuration

Abstract: A first detailed study of the ground state of the H + 3 molecular ion in linear configuration, parallel to a magnetic field direction, and its low-lying Σ, Π, ∆ states is carried out for magnetic fields

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The fact is that in both the H and H + 2 systems the binding energy grows dramatically with an increase of the magnetic field strength, it hints at the possible existence of unusual chemical species in strong magnetic fields. Other simple, traditional such as H + 3 [12,13], and exotic compounds mainly formed by protons and/or α-particles (helium nuclei) and one or two electrons have been studied to a certain degree. For a discussion, see [10] for one-electron systems and [14] for two-electron systems.…”
Section: Introductionmentioning
confidence: 99%
“…The fact is that in both the H and H + 2 systems the binding energy grows dramatically with an increase of the magnetic field strength, it hints at the possible existence of unusual chemical species in strong magnetic fields. Other simple, traditional such as H + 3 [12,13], and exotic compounds mainly formed by protons and/or α-particles (helium nuclei) and one or two electrons have been studied to a certain degree. For a discussion, see [10] for one-electron systems and [14] for two-electron systems.…”
Section: Introductionmentioning
confidence: 99%
“…All of them (or, at least, some of them) can be in the same quantum state, with the same spin projection and magnetic quantum number [6]. This situation was observed in H 2 [7] and H + 3 [8], where in a domain of large magnetic fields the ground state was given by the state of the maximal total spin but with the electrons having the same zero magnetic quantum number (see a discussion below). In [5] qualitative arguments were presented that such chains can be of any length, thus, can contain arbitrary many protons.…”
Section: Introductionmentioning
confidence: 99%
“…In[8] it is shown that the H + 3 molecular ion exists in a magnetic field as a bound state. For B 0.2 a.u.…”
mentioning
confidence: 99%
“…Magnetic fields for which He 2+ 2 does not exist (see text) are marked by ( * ) . Total energy E T (He + (1s 0 ) + He + (1s 0 )) (in Ry) for zeroing total electron spin projection from[2] is shown for a comparison.…”
mentioning
confidence: 99%